A IMPORTÂNCIA DAS TICS E DA EDUCAÇÃO COMO PROCESSO COMUNICACIONAL DIALÓGICO NO ENSINO SUPERIOR: Um Estudo da Universidade Estadual de Mato Grosso do Sul - REIS, ANA TEREZA VENDRAMINI (2016)
This thesis has aimed at finding out how the faculty of the State University of Mato Grosso do Sul (UEMS) realizes, understands and reacts to the incorporation and to the use of Information and Communication Technologies (ICTs) in undergraduate courses of the Institution, considering the new dialogical communication processes that the ICTs may provide in today's society. Methodologically, the thesis consists of bibliographic research, seeking to support the areas of education and communication, as well as Educommunication; documentary research to contextualize the research locus and exploratory research from the application of an online questionnaire to 165 professors of UEMS, who answered it voluntarily. It was found that professors use ICTs in their daily personal activities and, to a lesser extent, in professional environments. The challenges are to better form those professors and to provide them with continuous training so that they can use the ICTs in classrooms more effectively. It is also noted that advances in technology and new communicational ecosystems built new and other realities, making learning a nonlinear factor, demanding revision in educational projects in higher education so that they enable purposeful dialogues between communication and education. The institutional infrastructure regarding the ICTs is another obstacle pointed out, both in the acquisition and in the maintenance of those technological devices made by the University. In the end, it is proposed to carry out studies and research to discuss changes in the faculty’s employment contract arrangements, since working with ICTs properly requires more time and teaching dedication.